Osiris revisited: confirming a solar metallicity and low C/O in HD 209458 b - Bachmann, Nora; Kreidberg, Laura; Mollière, P.; Deming, D.; Tsai, S.-M. (Astronomy and astrophysics, 2025)
HD 209458 b is the prototypical hot Jupiter and one of the best targets available for precise atmosphere characterisation. Now that spectra from both the Hubble Space Telescope (HST) and the James Webb Space Telescope (JWST) are available, we can reveal the atmospheric properties in unprecedented detail. For this study we performed a new data reduction and analysis of the original HST/WFC3 spectrum, accounting for the wavelength dependence of the instrument systematics that was not considered in previous analyses. This allowed us to precisely and robustly measure the much-debated H2O abundance in HD 209458 b’s atmosphere. We combined the newly reduced spectrum with archival JWST/NIRCam data and ran free chemistry atmospheric retrievals over the 1.0 − 5.1 μm wavelength range, covering possible features of multiple absorbing species, including CO2, CO, CH4, NH3, HCN, Na, SO2, and H2S. We detected H2O and CO2 robustly at above 7σ significance, and found a 3.6σ preference for cloudy models compared to a clear atmosphere. For all the other absorbers we tested, only the upper limits of the abundance can be measured. We used Bayesian model averaging to account for a range of different assumptions about the cloud properties, resulting in a water volume mixing ratio of 0.95−0.17+0.35× solar and a carbon dioxide abundance of 0.94−0.09+0.16× solar. Both results are consistent with solar values and are comparable to predictions from the VULCAN 1D photochemistry model. Combining these values with a prior on the CO abundance from ground-based measurements, we derive an overall atmospheric composition comparable to solar metallicity of [M/H] = 0.10−0.400.41 and very low C/O of 0.054−0.034+0.080 with a 3 σ upper limit of 0.454. This indicates a strong enrichment in oxygen and depletion in carbon during HD 209458 b’s formation.
Online veröffentlicht: 11. August 2025
Gesehen am 16.01.2026